Optimizing the Wukuf-”˜Arafah Time Determination Model According to the Governments of Saudi Arabia and Indonesia - Nihayatur Rohmah (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2022)
Eid al-Adha is a historic moment for Muslims not only in Indonesia but also for Muslims around the world. Based on astronomical reckoning data, it is known that determining the beginning of the month of Dzulhijja 1443 H is essential to have a difference. This is interesting to study because it has an impact on Muslims. For the government of Saudi Arabia, the Ummul Qura calendar is a civil calendar used for administrative purposes. Meanwhile, for the sake of worship, determining religious days in one of them determines that Ramadan, Shawwal, and Dzulhijja become the authority of the al-Qodi al-a'la assembly. The Government of Indonesia, through the Ministry of Religion as of Ramadan 1443 H, has used the MABIMS New Criteria in determining the beginning of the Hijriya month so that with the enactment of this new criterion, there is a difference in determining the time of Wukuf-Arafah between the Saudi and Indonesian Governments. Based on these differences in determination, two problem formulations want to be studied further. First, how do the Saudi and Indonesian Governments use the model/method in determining the time of wukuf-arafah, and secondly, for Muslims with differences in determining the time of wukuf-arafah? To answer the formulation of the problems, this study analyzes it based on the Ummul Qura Calendar system used by the Saudi Government and Imkanur rukyat with the new MABIMS criteria used by the Indonesian Government. One application of the new MABIMS criteria in Indonesia is the difference in Eid al-Adha between the Government of Indonesia and one of the religious mass organizations, Muhammadiyah. Another implication is that various polemics are developing in the community regarding whether or not fasting the Sunnah of Arafah is different from the determination of the day of Wukuf.